Takaful Sebagai Alternatif Kepada Aqilah Dalam Menjelaskan Pampasan Kepada Pihak Ketiga: Perbincangan Isu-isu Fiqh Berbangkit: Takaful as the Alternative to ‘Aqilah in Third Party Indemnity: A Study on Fiqh Related Issues - Abdul Khalil, Shahidra; Ali, Abdul Karim; Hj Abdullah, Luqman (Jurnal Fiqh, 2017)
Since 1973, the rights of traffic accident victims in Malaysia have been protected by the law through mandatory obligation to all vehicle owners to be insured against third party risk since 1973. Despite offering a good service of preparing a promising fund as compensation for the injury or fatality inflicted upon third parties in traffic accidents, third party insurance is still considered haram (impermissible) by Islamic scholars due to its non-compliant operation with several Islamic principles. As an alternative, Takaful which is in line with the Islamic principle of mutual assistance has been financially institutionalised in 1984 in Malaysia. In terms of Takaful’s role in indemnifying compensation for third parties in accident cases, many contemporary scholars associate the concept of Motor Takaful with ‘aqilah. Therefore this paper aims to study the relation between Takaful and ‘aqilah. Is Takaful a compatible analogy (qiyas) to ‘aqilah or does it only serve as an alternative to the institution which is non-existent in the modern world as its form was in the early days of Islam. Furthermore, several issues relating to ‘aqilah’s role in paying diyat to the third party is discussed such as the membership of ‘aqilah. As Islamic scholars opine that ‘aqilah’s members must be from the same religion, must the same requirement be applied to Takaful? Based on comparative analysis, the study has shown that although Takaful and ‘aqilah are based on mutual cooperation or al-tanasur principle, there are significant differences between the concepts of these two institutions. Hence, Takaful is not analogical to ‘aqilah but an alternative only. Therefore, Takaful operation is not bound to all the rulings in ‘aqilah. This also denotes that Motor Takaful fund which is contributed by the participants, be it Muslims or non-Muslims may be used as compensation to the third party on behalf of the negligence of any Takaful participants in their driving.